At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To find the domain of the composite function [tex]\((f \circ g)(x)\)[/tex], where [tex]\(f(x) = \frac{1}{x-1}\)[/tex] and [tex]\(g(x) = \frac{1}{x+4}\)[/tex], we need to follow these steps:
1. Find the domain of [tex]\(g(x)\)[/tex]:
- [tex]\(g(x)\)[/tex] is defined as [tex]\(\frac{1}{x+4}\)[/tex].
- The function [tex]\(g(x)\)[/tex] will be undefined when the denominator is zero, i.e., [tex]\(x + 4 = 0\)[/tex] which gives [tex]\(x = -4\)[/tex].
- So, the domain of [tex]\(g(x)\)[/tex] is all real numbers except [tex]\(x = -4\)[/tex], which can be expressed as:
[tex]\[ (-\infty, -4) \cup (-4, \infty) \][/tex]
2. Find the composite function [tex]\((f \circ g)(x)\)[/tex]:
- The composite function [tex]\((f \circ g)(x)\)[/tex] is given by [tex]\(f(g(x))\)[/tex].
- Substituting [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex], we get:
[tex]\[ (f \circ g)(x) = f\left(\frac{1}{x+4}\right) \][/tex]
- Next, we substitute [tex]\(\frac{1}{x+4}\)[/tex] into [tex]\(f(x) = \frac{1}{x-1}\)[/tex]:
[tex]\[ f\left(\frac{1}{x+4}\right) = \frac{1}{\left(\frac{1}{x+4}\right) - 1} = \frac{1}{\frac{1 - (x+4)}{x+4}} = \frac{1}{\frac{-x-3}{x+4}} = \frac{x+4}{-x-3} \][/tex]
3. Determine where [tex]\( (f \circ g)(x) \)[/tex] is undefined:
- [tex]\((f \circ g)(x)\)[/tex] will be undefined where [tex]\(g(x)\)[/tex] is undefined, i.e., at [tex]\(x = -4\)[/tex].
- In addition, [tex]\((f \circ g)(x)\)[/tex] will be undefined where [tex]\(f(g(x))\)[/tex] is undefined:
- [tex]\(f(x) = \frac{1}{x-1}\)[/tex] is undefined when [tex]\(x = 1\)[/tex].
- Solve [tex]\(g(x) = 1\)[/tex]:
[tex]\[ \frac{1}{x+4} = 1 \implies x+4 = 1 \implies x = -3 \][/tex]
- Hence, [tex]\((f \circ g)(x)\)[/tex] is undefined at [tex]\(x = -3\)[/tex].
4. Combine the results:
- The domain of [tex]\((f \circ g)(x)\)[/tex] combines the restrictions from [tex]\(g(x)\)[/tex] and the places where the composite function is undefined.
- Therefore, the domain of [tex]\((f \circ g)(x)\)[/tex] is:
[tex]\[ (-\infty, -4) \cup (-4, -3) \cup (-3, \infty) \][/tex]
Thus, the correct answer is:
[tex]\[ (-\infty, -4) \cup (-4, -3) \cup (-3, \infty) \][/tex]
1. Find the domain of [tex]\(g(x)\)[/tex]:
- [tex]\(g(x)\)[/tex] is defined as [tex]\(\frac{1}{x+4}\)[/tex].
- The function [tex]\(g(x)\)[/tex] will be undefined when the denominator is zero, i.e., [tex]\(x + 4 = 0\)[/tex] which gives [tex]\(x = -4\)[/tex].
- So, the domain of [tex]\(g(x)\)[/tex] is all real numbers except [tex]\(x = -4\)[/tex], which can be expressed as:
[tex]\[ (-\infty, -4) \cup (-4, \infty) \][/tex]
2. Find the composite function [tex]\((f \circ g)(x)\)[/tex]:
- The composite function [tex]\((f \circ g)(x)\)[/tex] is given by [tex]\(f(g(x))\)[/tex].
- Substituting [tex]\(g(x)\)[/tex] into [tex]\(f(x)\)[/tex], we get:
[tex]\[ (f \circ g)(x) = f\left(\frac{1}{x+4}\right) \][/tex]
- Next, we substitute [tex]\(\frac{1}{x+4}\)[/tex] into [tex]\(f(x) = \frac{1}{x-1}\)[/tex]:
[tex]\[ f\left(\frac{1}{x+4}\right) = \frac{1}{\left(\frac{1}{x+4}\right) - 1} = \frac{1}{\frac{1 - (x+4)}{x+4}} = \frac{1}{\frac{-x-3}{x+4}} = \frac{x+4}{-x-3} \][/tex]
3. Determine where [tex]\( (f \circ g)(x) \)[/tex] is undefined:
- [tex]\((f \circ g)(x)\)[/tex] will be undefined where [tex]\(g(x)\)[/tex] is undefined, i.e., at [tex]\(x = -4\)[/tex].
- In addition, [tex]\((f \circ g)(x)\)[/tex] will be undefined where [tex]\(f(g(x))\)[/tex] is undefined:
- [tex]\(f(x) = \frac{1}{x-1}\)[/tex] is undefined when [tex]\(x = 1\)[/tex].
- Solve [tex]\(g(x) = 1\)[/tex]:
[tex]\[ \frac{1}{x+4} = 1 \implies x+4 = 1 \implies x = -3 \][/tex]
- Hence, [tex]\((f \circ g)(x)\)[/tex] is undefined at [tex]\(x = -3\)[/tex].
4. Combine the results:
- The domain of [tex]\((f \circ g)(x)\)[/tex] combines the restrictions from [tex]\(g(x)\)[/tex] and the places where the composite function is undefined.
- Therefore, the domain of [tex]\((f \circ g)(x)\)[/tex] is:
[tex]\[ (-\infty, -4) \cup (-4, -3) \cup (-3, \infty) \][/tex]
Thus, the correct answer is:
[tex]\[ (-\infty, -4) \cup (-4, -3) \cup (-3, \infty) \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.